1996
DOI: 10.1136/adc.74.3.228
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation in paediatric patients: dose requirements and complications.

Abstract: The lack of oral anticoagulant guidelines specific to paediatric practice has led to the adoption of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…The epidemiology of venous TE within the tertiary paediatric setting has been reported in the international literature with increasing frequency. 1,3,4,[7][8][9][10][11][12][13][14][15][16][17] Whether these international descriptions reflect local experience has not previously been investigated. The use of differing medical and surgical approaches to conditions such as cancer, congenital heart disease and gastrointestinal disorders may well yield variable thrombotic complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of venous TE within the tertiary paediatric setting has been reported in the international literature with increasing frequency. 1,3,4,[7][8][9][10][11][12][13][14][15][16][17] Whether these international descriptions reflect local experience has not previously been investigated. The use of differing medical and surgical approaches to conditions such as cancer, congenital heart disease and gastrointestinal disorders may well yield variable thrombotic complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…In children after cardiac surgery for prosthetic valve replacement or the Fontan operation, oral anticoagulation therapy is used for primary prophylaxis against thromboembolism. [1] The paediatric experience is, however, somewhat limited and guidelines are usually derived from the adult recommendations. [2] In general, a target international normalised ratio (INR) of 2.0–3.0 is aimed for post‐Fontan surgery or secondary prophylaxis after thromboembolic complications, and INR of 3.0–4.0 for mechanical valve replacement.…”
mentioning
confidence: 99%
“…[2] In general, a target international normalised ratio (INR) of 2.0–3.0 is aimed for post‐Fontan surgery or secondary prophylaxis after thromboembolic complications, and INR of 3.0–4.0 for mechanical valve replacement. [1,2]…”
mentioning
confidence: 99%
“…Because LMWH,14‐16 warfarin,17, 18 and aspirin19 have already been reported to be effective for the prevention of recurrent venous thromboembolism, these reports support anticoagulant therapy by our alternative regimen to prevent PVS following IVR. In addition, the safety of anticoagulant therapy has been reported for pediatric populations 20‐24. We concluded that stronger anticoagulation is necessary for preventing recurrent PVS, although this 3‐agent anticoagulant therapy combining LMWH, warfarin, and aspirin may cause an excessive anticoagulant state.…”
Section: Discussionmentioning
confidence: 88%